Role of Photic and Thermal Stimuli in Production of the Oestrus-inducing Pheromone in Field Mice - Dixit*, Himanshu (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Sixty adult males divided in six equal groups were exposed to different photoperiods for 21 days. Exposures included natural lights (ca 11 hr), long photoperiod (16L: 8D) and short photoperiod (8L: 16D). The first three groups received these exposures at room temperature (36-380C). Soiled bedding of the above males was introduced in the cages of unisexually housed noncyclic females and their potentiality to induce oestrus was assessed. It was observed that the bedding of all the males proved to be a stimulus inducing oestrus in majority of females during 7 days exposure. There was no significant difference in the number of female returning to oestrus following exposure to soiled beddings of different stimulus males.Ã‚Â  These results lead to conclude that environmental factors, especially light and temperature do not influence the production / release of the primer pheromone inducing oestrus in noncyclic Indian field mice.